Critical Review: When the Party is Over. (1st November 2016) - Carrico, Adam W.; Zepf, Roland; Meanley, Steven; Batchelder, Abigail; Stall, Ronald
Abstract : Abstract: Because problematic patterns of alcohol and other substance use are prevalent drivers of the HIV/AIDS epidemic, comprehensive interventions are needed for substance-using men who have sex with men (SUMSM). We conducted a systematic review of 12 randomized controlled trials (RCTs) of behavioral interventions for reducing condomless anal intercourse (CAI) in SUMSM. Three RCTs observed that cognitive behavioral or motivational interviewing interventions achieved a 24% to 40% decrease in CAI. Interventions also tended to demonstrate greater efficacy for reducing CAI and substance use among those who had lower severity of substance use disorder symptoms. Although behavioral interventions for SUMSM are one potentially important component of biobehavioral HIV/AIDS prevention, further research is needed to examine whether integrative approaches that cultivate resilience and target co-occurring syndemic conditions demonstrate greater efficacy. Multilevel intervention approaches are also needed to optimize the effectiveness of pre-exposure prophylaxis and HIV treatment as prevention with SUMSM.